2023
DOI: 10.2147/ndt.s398838
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience and Stress Coping Styles in Migraine Patients

Abstract: It was aimed to determine the level of psychological resilience and to investigate the psychological and clinical parameters that affect the resilience level in migraine patients. Patients and Methods: A total of 100 migraine patients and 100 healthy controls who agreed to participate in the study filled in the sociodemographic data form and also Beck Anxiety Scale, Beck Depression Scale, Psychological Resilience Scale for Adults, Perceived Stress Scale, Stress Coping Styles Scale, and Psychological Well-Being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Consistent with our correlation findings, the ANOVA performed revealed that patients with migraine with medium CR reported significantly lower levels of depression and an increased sense of pleasure in life, as well as lower pain interference, compared to those with medium-to-low CR. Hence, also these results point to the need of promoting, especially in migraine patients, problem-and support-oriented coping strategies (14,38) that could prevent cognitive, emotional, and functional impairment.…”
Section: Original Research Articlementioning
confidence: 75%
See 1 more Smart Citation
“…Consistent with our correlation findings, the ANOVA performed revealed that patients with migraine with medium CR reported significantly lower levels of depression and an increased sense of pleasure in life, as well as lower pain interference, compared to those with medium-to-low CR. Hence, also these results point to the need of promoting, especially in migraine patients, problem-and support-oriented coping strategies (14,38) that could prevent cognitive, emotional, and functional impairment.…”
Section: Original Research Articlementioning
confidence: 75%
“…Following this new paradigm, the cognitive dimension results as a vital component of the subjective perception of pain requiring cognitive-evaluation, learning, recall of past experi-ences, and active decision making. Most clinical studies, focused on neurological disorders such as migraine, have found an impairment of cognitive abilities (14,15). This remarks the close connection between pain and cognitive functioning (16,17).…”
Section: Introductionmentioning
confidence: 94%
“…In a study conducted by Oguz A. et al at Dokuz Eylül University in 2002 was determined that epilepsy-related factors such as duration of epilepsy, seizure frequency, and polytherapy increased anxiety and depression, while seizure onset age, seizure type, and electroencephalographic findings were not associated with anxiety and depression [34]. In our study, as in Dokuz Eylul, seizure onset age, seizure type, and EEG findings were not correlated with RCADS-CV depression scores, but unlike the study, RCADS-CV depression scores were also found to be unrelated with gender, number of siblings, frequency of seizures, seizure type, seizure time, AED type and polytherapy (Table 4,5).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of migraine is not well understood but it is hypothesized that is a multifactorial disease influenced by numerous factors including genetic, epigenetic but also lifestyle, personal history and environmental factors [ 76 , 90 ]. People living in areas with high air pollution, exposure to toxins, lack of access to water, frequent changes in weather conditions, and poor nutrition experience greater psychosocial stress, which affects the course of the disease [ 91 , 92 ].…”
Section: Stigma and Social Determinantsmentioning
confidence: 99%